Electrochemical study of butylate: application to the analysis of water - Barroso, M. Fátima (2013)
The electroactivity of butylate (BTL) is studied by cyclic voltammetry (CV) and square wave voltammetry (SWV) at a glassy carbon electrode (GCE) and a hanging mercury drop electrode (HMDE). Britton–Robinson buffer solutions of pH 1.9–11.5 are used as supporting electrolyte. CV voltammograms using GCE show a single anodic peak regarding the oxidation of BTL at +1.7V versus AgCl/ Ag, an irreversible process controlled by diffusion. Using a HMDE, a single cathodic peak is observed, at 1.0V versus AgCl/Ag. The reduction of BTL is irreversible and controlled by adsorption. Mechanism proposals are presented for these redox transformations. Optimisation is carried out univaryingly. Linearity ranges were 0.10–0.50 mmol L-1 and 2.0–9.0 µmolL-1 for anodic and cathodic peaks, respectively. The proposed method is applied to the determination of BTL in waters. Analytical results compare well with those obtained by an HPLC method.